Análisis sistemático sobre estilos de crianza que influyen en conductas agresivas en los niños, niñas y adolescentes en el contexto escolar (2024)
The general objective of this research is the characterization of parenting styles that influence aggressive behaviors in children and adolescents in the school context in the last five years, through a literature review of the information, with descriptive qualitative methodology, by means of a database and meta search engines where the legitimacy and relevance of the articles proposed by the academy is guaranteed through the use of the PRISMA 2020 statement or method; which aims to facilitate the transparency of information in systematic reviews.